Context-dependent multifunctionality of galectin-1: a challenge for defining the lectin as therapeutic target - Smetana, Karel; André, Sabine; Kaltner, Herbert; Kopitz, Jürgen; Gabius, Hans-Joachim (Expert opinion on therapeutic targets, 2013)
INTRODUCTION: One route of translating the information encoded in the glycan chains of cellular glycoconjugates into physiological effects is via receptor (lectin) binding. A family of endogenous lectins, sharing folding, a distinct sequence signature and affinity for β-galactosides (thus termed galectins), does so effectively in a context-dependent manner. AREAS COVERED: An overview is given on the multifunctional nature of galectins, with emphasis on galectin-1. The broad range of functions includes vital processes such as adhesion via glycan bridging, glycoconjugate transport or triggering signaling relevant, for example, for growth regulation. Besides distinct glycoconjugates, this lectin can also interact with certain proteins so that it can target counterreceptors at all sites of location, that is, in the cytoplasm and/or nucleus, at both sides of the membrane or extracellularly. Approaches to strategically exploit galectin activities with therapeutic intentions are outlined. EXPERT OPINION: The wide versatility of sugar coding and the multifunctionality of galectin-1 explain why considering to turn the protein into a therapeutic target is an ambitious aim. Natural pathways shaped by physiologic master regulators (e.g., the tumor suppressor p16(INK4a)) are suggested to teach inspiring lessons as to how the lectin might be recruited to clinical service.
Keywords: Animals; biologický transport; proliferace buněk; Glycoconjugates; galektin 1; glykokonjugáty; Neoplasms; nádory; buněčná adheze; cílená molekulární terapie; lidé; Galectins; Antineoplastic Agents; protinádorové látky; Cell Adhesion; signální transdukce; Signal Transduction; Galectin 1; Biological Transport; galektiny; racionální návrh léčiv; Cell Proliferation; nádorové proteiny; Neoplasm Proteins; Drug Design; zvířata; Molecular Targeted Therapy; Humans